Community pharmacist-led medication review procedures across Europe: characterization, implementation and remuneration - LeilaImfeld-Isenegger, Tamara (2021)
Background: Pharmaceutical Care Network Europe (PCNE) proposed a definition and classification system (type 1, 2a, 2b, 3) for medication review in 2016. However, to date, a description of the implementation and remuneration of such procedures across Europe is lacking. Objective: The aim of this study was to describe the medication review procedures and the level of implementation and remuneration in community pharmacies across Europe. Methods: An online survey was developed to characterize medication review procedures (PCNE classification), level of implementation (considering regional or national) and remuneration by a third party. This survey was sent to a purposive sample of three individuals per country, with a working background in community pharmacy, pharmacy practice research, or health policy to ensure reliable data. Data triangulation was used and consensus sought between the responses. Results: Data were received from 34 out of 44 targeted European countries (November 2016–October 2017) [response rate = 77%]. Overall, 55.9% of the countries provided at least one type of medication review as an implemented service or project. Type 1 medication review (based on the medication history) was provided in 13 countries, type 2a (medication history + patient interview) in 14, type 2b (medication history + clinical data) in two, and type 3 medication review (medication history + patient interview + clinical data) in four countries. Ten of the mentioned services or projects were remunerated by a third-party. Conclusion: Substantial heterogeneity was observed across Europe in various aspects, including the procedures, implementation level and remuneration obtained. Type 1 and 2a medication review services seem to be more feasible to implement in the community pharmacy than type 2b and 3. A large number of medication review projects were ongoing in community pharmacies, which suggests that new medication review services could become implemented in the coming years.